The Killing Power of Areca Seed Extract (Areca catechu L.) in the Control of Cockroaches (Periplaneta americana) - Haryati Wahyu Kusuma Pertiwi; Susilawati; Suharno (POLTEKKES KEMENKES PONTIANAK, 2021)
Abstract. Cockroaches are one of the insects that can spread diseases such as dysentery, diarrhea, cholera, viral hepatitis. Therefore an insecticide that is safe for the environment is needed, one of which is areca seed (Areca caechu L.) which contains Polyphenols, Flavonoids, Tanins, and Alkaloids that are safe for the surrounding environment and do not leave high residues. The purpose of this study was to analyze the strength test to kill areca seed extract (Areca catechu L.) against cockroach populations. The research design used in this research is quasi experimental (Quasi Experimental), the sample in this study used 360 adult cockroaches (Periplaneta americana) measuring 3 cm. This study used the Mann-Whitney U test analysis to analyze the differences in the ability of areca seed extract (Areca catechu L.) in killing cockroach populations. The results showed that at a concentration of 100% it was more effective to kill cockroaches Periplaneta americana type because it can kill 91% of American perennial cockroaches within 24 hours. The conclusion of this study is that there are differences in concentration of areca catechu L. extract with variations of 80%, 90%, 100% where p = 0.000.